Monte Carlo simulation of CdTe thin film recrystallization process during chlorine activation. (27th January 2020) - Zhu, Ziyao; Liu, Xiangxin; Zhang, Yue; Zhang, Yufeng; Wu, Qiuchen; Lin, Xinlu
Abstract: In this work we studied the grain growth and orientation change of CdTe multi-crystallize thin films during chlorine activation. A thermodynamic energy criterion is proposed for finding non-toxic substitutes of cadmium chloride and tested by Monte-Carlo simulation method combined with CASTEP calculation and annealing algorithm. Visualized pixel images of simulation results are in good agreement with experimental results. The mechanism of cadmium chloride for chlorine activation is explained from the aspect of thermodynamics. Predictions of non-toxic chloride substitutes for toxic cadmium chlorine and corresponding annealing routes are given based on the proposed energy criterion and energy calculation results.